The research of burning technology of water coal fuel got from shubarkul coal - Kussaiynov, K.; Tanasheva, N.K.; Tolynbekov, A.; Alpysova, G.K.; Tleubergenova, A.Zh. (Publishing House of the KarSU named after E.A.Buketov, 2014)
Modern development of power system is characterized by the decrease of using expensive liquid fuel which is a valuable raw material for the oil refining industry and the increase of using solid fuels. Stocks of high-quality coal deposits are exhausted due to increase in a share of solid fuels. Besides, there is deterioration in a quality of solid fuels extracted by mining method. Transition to the development of powerful coal deposits mined by open way and the use of it as fuel for power plants and other fuel using devices are connected with certain difficulties. And mainly it is because of high cost and power consumption of preparation process for burning.
Keywords: fuel; coal; water coal fuel; nozzle; coal; installation; burning